Post-Preparation Total Motile Sperm Count in Infertile Men and The Success Rate of Intrauterine Insemination at Rumah Sakit Kasih Ibu Denpasar in 2022 - Wibawa, I Kadek Sadam; I Gusti Ngurah Pramesemara; I Made Oka Negara; I Gusti Ayu Widianti (Universitas Airlangga, 2024)
Background: Every married couple hopes to have children, but not all can fulfil that desire. A married couple finds themselves unable to achieve pregnancy after 12 months of regular unprotected sexual intercourse, which can be called infertility. Infertility can also occur in men. In dealing with infertility, intrauterine insemination (IUI) is a cost-effective and non-invasive Assisted Reproductive Technology (ART) procedure. The condition of male infertility can be detected through semen analysis. One of the parameters in semen analysis is the total motile sperm count (TMSC). Objective: This research seeks to establish the relationship between post-preparation TMSC and the success rate of the IUI procedure. Methods: This research adopts a descriptive-analytical design employing a cross-sectional methodology. Non-probability sampling was utilized as the sampling technique, and the data analyzed were secondary data from the medical records of male patients aged 25 to 45 years old diagnosed with infertility. The subjects had undergone IUI at Rumah Sakit Kasih Ibu Denpasar from January 1 to December 31, 2022. Results: From the 35 obtained samples, 12 individuals (34.3%) had a post-preparation TMSC of â‰¥10 í— 106, while 23 individuals (65.7%) had a post-preparation TMSC of <10 í— 106. The success rate of the Intrauterine Insemination (IUI) procedure was 17.1%, with 4 couples (33.3%) having a post-preparation TMSC of â‰¥10 í— 106 and 2 couples (8.7%) with a post-preparation TMSC of <10 í— 106. The Fisher's Exact test carried out has obtained a result (p=0.151), while the value of the odds ratio (OR) obtained (OR=5.250) Conclusion: Based on statistical analysis, it can be concluded that there is no significant association between post-preparation TMSC in infertile men and the success rate of IUI procedures (p > 0.05). The odds ratio (OR) obtained is 5.250 (95% CI 0.799-34.496).